Deformation and structural evolution of metamorphic complexes of the Taldyk antiform in the East Mugodzhar zone of Urals (West Kazakhstan) - B. G. Golionko; A. V. Ryazantsev (Геодинамика и тектонофизика)
The study is focused on mesostructural folded parageneses of the Taldyk antiform (a.k.a. Taldyk block) located in the East Mugodzhar zone. The sequence of their formation is established; the structural evolution of the study area is investigated, and four stages of deformation are identified. The NW-trending folds F1 with SE-vergence formed during the first stage of deformation, DI. The geodynamics and timeline of this stage remain unclear. The W-E-trending folds F2 with E-vergence are related to tectonic movements that took place at stage DII. In the western limb of the antiform, stage DII is evidenced by folds overturned towards the south-east. In the eastern limb, folds plunge to the east and northeast. These fold structures are probably related to the Devonian subduction-obduction processes. At stage DIII, thrusting of the Taldyk antiform over the West Mugodzhar zone and folding F3 with W-vergence is related to the Ural continental collision in the Late Paleozoic, which completed the geodynamic evolution of the Ural paleo-ocean. At stage DIV, postcollisional shearing is evidenced by folds F4 with steeply dipping hinges, which completed the structural evolution of the study area.